Second Washera and Wollo sheep improvement Workshop in Amhara region: Summary Report - Ferede, Yeshiwas; Getachew, Tesfaye; Belay, Berhanu; Yeheyis, Likawent; Rekik, Mourad; Haile, Aynalem (Bahir Dar University, 2022)
Since 2009, the International Centre for Agricultural Research in the Dry Areas (ICARDA) in partnership with the International Livestock Research Institute (ILRI), the University of Natural Resources and Life Sciences (BOKU) and Ethiopian NARS has been implementing community-based breeding program (CBBP) in Ethiopia, to support the livelihood of smallholder farmers by improving the productivity of small ruminants through selective breeding. Since then, a remarkable progress has been made in improving the livelihood of small holders in different parts of the country. Currently, the CBBP initiative has been expanded to cover more than 10,000 households in Ethiopia. Generally, improved productivity, higher offtake, and higher annual income were recorded in those households participating in CBBPs. For example, an average genetic gain of 0.20kg per year for six-months weight and, and increased mutton consumption (from 1 sheep to 3 slaughtered/year/HH) were achieved in CBBP intervention areas. ICARDA has been working on Menz sheep and Abergelle goat CBBPs improvement closely with the Amhara Regional Agricultural Research Institute (ARARI) and Amhara Region Bureau of Agriculture to transform small ruminant value chains in Amhara region and beyond. CBBPs is adapted by different institutions in the region and being expanded in many parts of the region. As an example, Washera sheep CBBPs and Wollo sheep improvement has been implemented by various institutions (different universities, research centers and the Ethiopian Biodiversity Institute). However, there is no a harmonized breeding objective, CBPP implementation modality and a clear roles and responsibility shared among stakeholders working in the region. Hence, bringing all institutions together and harmonizing the scattered efforts in Washera and Wollo sheep improvement is crucial to bring impact at scale. As part of the joint effort, it has been recalled that ICARDA in collaboration with ARARI organized a two-day consultation and planning workshop in Bahir Dar at Unison Hotel from 14-15 April 2022. Since then, as per the agreements of implementation modality during the first consultative workshop, various activities were performed by the respective stakeholders. To evaluate such progresses made so far, the second consultative workshop was organized by ICARDA and ARARI on October 04, 2022 in BenMas Hotel, Bahir Dar. A total of 27 participants from different partnering institutes attended the consultative workshop.